Ferramenta para a identificação do potencial silvicultural regional - Weiler, Elenice Broetto (2021)
The demand for wood and products from planted forests will increase given the prospect of population growth. Thus, the expected need to increase areas with forest plantations for the next decades, in line with the development of the regions, is a fundamental topic of debate. Would the Rio Grande Sul have potential territory for production? Is the State prepared for this market? Could small rural properties be part of this future scenario? Could new investments add to regional development? The main focus of the thesis was the verification of the silvicultural potential in terms of spatial distribution in the northern Rio Grande do Sul, with a case study in Corede Celeiro. The proposal to create a Normalized Silvicultural Index categorized 21 municipalities into classes with different potentials for planting (Excellent, Very Good, Good, Low, and Inapt). The municipalities were characterized to understand the dynamics related to socioeconomic and human development, by verifying areas cultivated with forestry, through the quantification and mapping of forest plantations. Also, the lack of a pattern of plantations distribution was verifyed, from the relationship with the geomorphological characterization and the proposal of a normalized linear model based on multivariate information of physical, social and economic aspects. Thus, it was possible to georeference, spatialize and integrate information, promoting the territory recognition, with an understanding of which factors and what weight each has on the municipal scale, reflecting in the categorization of a silvicultural potential. In this way, the results of this thesis will serve as a tool for public authorities to include planted forests in sustainable development plans, as well for planning silvicultural activities, as the private sector, in line with the specificities of the environment. The proposal is also in line with new methodological possibilities that may contribute to adapting to changes in territorial planning, licensing, and development projects for silvicultural activities.